The genome sequence of a soldier fly, Nemotelus pantherinus (Linnaeus, 1758) [version 1; peer review: 2 approved] - Olga Sivell; Ryan Mitchell; Anthony Irwin (Wellcome Open Research)
We present a genome assembly from a male specimen of Nemotelus pantherinus (soldierfly; Arthropoda; Insecta; Diptera; Stratiomyidae). The genome sequence has a total length of 804.69 megabases. Most of the assembly (95.93%) is scaffolded into 6 chromosomal pseudomolecules, including the X and Y sex chromosomes. The mitochondrial genome has also been assembled, with a length of 19.1 kilobases. Gene annotation of this assembly on Ensembl identified 27,389 protein-coding genes.